Pineal Protein Kinase: Effect of Enzymic Phosphorylation on Actinomycin D Binding by, and Template Activity of, Chromatin - Fontana, Joseph A. (1973)
The ability of protein kinase from bovinepineal gland to phosphorylate calf-thymus chromatin and thereby to alter the association between chromatin DNA and histones was investigated. Phosphorylation of calf-thymus chromatin by pineal protein kinase results in an apparent decreased binding between the histones and DNA in chromatin, as indicated by (i) an increase in actinomycin D-binding sites after phosphorylation and (ii) an increase in the template capacity of the calf-thymus chromatin after phosphorylation. F(1) histone and F(3) histone are the major histone classes in the chromatin that are phosphorylated by the protein kinase. These results support the hypothesis that pineal protein kinase may function at the transcriptional level.